Relationship Quality and Cost-to-Serve as the Key of Building Customer Value - Miftahurrohman Miftahurrohman; Hendri Rasminto; Pemilia Sulistyowati; Risma Nurhapsari (Universitas Sains dan Teknologi Komputer, 2022)
This study examines the creation of Customer Value with the supporting variables Relationship Quality and Cost-to-Cost as variables that can affect value. Customer Value for the company in building relationships in the future. This research takes companies that supply fabric dyes to textile companies by conducting interviews via email and in-person interviews. The method used is to examine qualitatively and quantitatively. In qualitative research, it examines the costs incurred which have a correlation with customer service and the estimated actual costs for individual services. Furthermore, quantitative measurements are carried out to check the quality of RQ, profitability from past customers, Customer Lifttime Value (CLV) by presenting the proposed framework. In the final section, an evaluation of the effect of RQ on CLV is carried out which results in the conclusion that RQ has an effect on driving customer costs and profitability in the future.